Development Of Gluten Free Moringa Choux Paste As A Culinary Tourism Product - Cica Yulia; Sri Subekti (Universitas Pendidikan Ganesha, 2022)
Bandung is known as the city of culinary tourism, because there are so many culinary delights that tourists can enjoy when visiting the city of Bandung. The characteristics of cakes that are widely sold as souvenirs are bakery and pastry products. Pastry and bakery products use flour as the basic ingredient. For some consumers who have health problems, products made from wheat flour cannot be consumed because they can affect their health status. Choux paste is a type of pastry with light characteristics and soft texture with the basic ingredients of wheat flour. One effort to replace the use of gluten in wheat flour is to optimize the use of local food ingredients that are gluten-free, such as rice flour and glutinous rice flour. The addition of Moringa leaf flour has the potential as a natural dye and is rich in vitamins, minerals and amino acids. The author innovates to make a gluten free Choux Paste product with the addition of Moringa leaves (moringa oleifera) which contains fiber and complete vitamins to increase nutritional content and is good for consumption by the general public so that it has the potential to become a culinary tourism product. The purpose of this research is to develop gluten Free moringa Choux Paste as a culinary tourism product. The research method is experimental. The results showed that the formula with the addition of 6g of Moringa leaf flour was the formula with the highest acceptability and the color was most favored by the panelists, so it was highly recommended. Keywords: Choux Paste, Gluten free flour, Moringa flour, Culinary tourism product